Effects of monocrotophos pesticide on steroidogenesis and transcription of steroidogenic enzymes in rainbow trout RTG-2 cells involving the protein kinase A signal pathway. Issue 1 (February 2015) - Wang, Zhenyu; Zhang, Xiaona; Tian, Hua; Wang, Wei; Ru, Shaoguo
Highlights MCP promoted the expression of steroidogenic enzymes in rainbow trout cells. MCP dysregulated the production of steroid hormones 17β-estradiol and testosterone. MCP disrupted the biosynthesis of sex hormones via the PKA signaling pathway.